Analysis of the Outcomes of the Alignment Activity in the Marketing Department of PT X - Raghda Pauwah; Ainur Komariah; Maria Puspita Sari (Universitas Mercu Buana, 2026)
This study aims to analyze the outcomes of the Alignment activity implemented in the Marketing Department of PT X, a batik manufacturing company located in Central Java, in aligning the company’s vision and mission and enhancing team work effectiveness. The study employs a quantitative research method using a Likert-scale questionnaire and open-ended questions administered to 11 employees who participated in the alignment activity. Data analysis was conducted through the calculation of mean scores, evaluation of open-ended responses, and validity testing using Pearson correlation. The results indicate that the alignment activity received a positive response, with the highest mean score observed in the internal communication aspect (4.37), followed by the collaboration aspect (91.27). However, the vision and mission understanding aspect obtained the lowest score (2.73), indicating the need for improvement in the methods used to communicate the company’s strategic direction. The validity test results show that five out of six questionnaire items were valid, while one item was found to be invalid. Overall, the alignment activity proved to be effective in improving employee communication, engagement, and collaboration; however, further reinforcement is required in enhancing employees’ understanding of the company’s vision and mission to ensure optimal achievement of strategic objectives.